2023
DOI: 10.1097/gme.0000000000002135
|View full text |Cite
|
Sign up to set email alerts
|

Urban-rural differences in epidemiology and risk factors of menopause syndrome in middle-aged Chinese women

Abstract: Objective: To compare the prevalence and severity of menopausal symptoms and investigate their associated factors among rural and urban middle-aged Chinese women.Methods: A descriptive, cross-sectional study of 4,580 urban and 2,729 rural randomly sampled participants aged 40 to 55 years in Gansu Province, China, was conducted. Questionnaires assessing the sociodemographic information and menstrual and reproductive histories of the participants were administered. The modified Kupperman scale was used to assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 40 publications
1
3
0
Order By: Relevance
“…We analysed the influencing factors of menopausal symptoms and found that women living in urban areas, with a positive mentality, a high sexual intercourse frequency, and regular physical exercise had a lower incidence of menopausal-related symptoms, which was consistent with the findings of Wang [ 25 ] and AN [ 26 ]. Women living in rural areas have fewer opportunities to receive menopause-related health education, have less understanding of the menopausal period, and cannot seek medical attention in a timely manner when menopausal symptoms occur, which in turn increases the possibility of menopausal symptoms [ 27 ].…”
Section: Discussionsupporting
confidence: 82%
“…We analysed the influencing factors of menopausal symptoms and found that women living in urban areas, with a positive mentality, a high sexual intercourse frequency, and regular physical exercise had a lower incidence of menopausal-related symptoms, which was consistent with the findings of Wang [ 25 ] and AN [ 26 ]. Women living in rural areas have fewer opportunities to receive menopause-related health education, have less understanding of the menopausal period, and cannot seek medical attention in a timely manner when menopausal symptoms occur, which in turn increases the possibility of menopausal symptoms [ 27 ].…”
Section: Discussionsupporting
confidence: 82%
“…In addition, a study from Poland comparing rural to urban postmenopausal women, demonstrated a higher prevalence of metabolic syndrome in the rural (70 %) than the urban group (22 %) [ 33 ]. Furthermore, two recent studies from Mexico [ 34 ] and China [ 35 ] have demonstrated that age at menopause is lower in rural than urban women. Earlier age at menopause is known to be associated with a higher risk of cardiovascular disease [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Earlier age at menopause is known to be associated with a higher risk of cardiovascular disease [ 36 ]. The study from China also showed that rural women had a higher prevalence of menopausal symptoms and that these were associated with a higher risk of non-communicable diseases [ 35 ]. These studies suggest than rural residence may be associated with a higher risk of CMDs in postmenopausal women, but longitudinal studies are required to determine whether the menopause transition is differentially associated with CMD risk in rural and urban populations.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that, as life expectancy increases, women live with menopause for about one-third of their lives. It is estimated that by 2030, a total of 1.2 billion women will be menopausal or postmenopausal [22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%